P 5 MCC950 treatment reduces neuroinflammation, rescues neuronal cell death and ameliorates motor deficits in the AAV1/2-A53T-αSyn mouse model of Parkinson's disease. (May 2022) - Grotemeyer, A.; Fischer, J.; Koprich, J.B.; Brotchie, J.M.; Volkmann, J.; Ip, C.W.
Abstract : Introduction: Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide. Aside from the known correlation with progressive α-Synuclein (αSyn) clustering, PD is also associated with neuroinflammation. An increased activity of the inflammasome and its main-component NOD-, LRR- and pyrin domain- containing protein 3 (NLRP3) – predominantly expressed in macrophages – is known for PD and mainly results in elevated Interleukin-1β (IL-1β) and a pro-inflammatory shift of the innate immune system. Recently, MCC950 (a potent inhibitor of NLRP3) was shown to result in significant neuroprotection in addition to reduced immune activity in the MPTP model. Here we tested the effects of MCC950 in the pathophysiological relevant Adeno-associated viral vector 1/2 (AAV1/2) – A53T- alpha synuclein (αSyn) mouse model of PD. Materials & Methods: The AAV1/2-A53T-αSyn mouse model was generated by unilateral viral vector injection in the substantia nigra (SN) (AP -3.1, ML 1.4, DV 4.4) and results in a profound dopaminergic neurodegeneration, pathological αSyn-clustering, and motor impairment. Over a period of 9 weeks mice received either 20mg/kgBW MCC950 or vehicle (NaCl 0, 9%) i.p. every other day. Behavioural changes were investigated using the cylinder and the rotarod performance test. Immunohistochemical stainings for immune cells (Cd11b+, CD4+, CD8+), αSyn+ profiles and dopaminergic neurons (tyrosine hydroxylase; TH+) were performed. Results: Treatment with MCC950 led to a significant attenuation of the innate and adaptive immune response in the SN of PD mice – indicated by reduced CD11b+ microglia cell size and numbers as well as reduced CD4+ and CD8+ T cell counts. These anti-inflammatory effects were accompanied by a significantly higher number of TH+ dopaminergic and Nissl+ neurons. Moreover, motor deficits were ameliorated in PD mice by MCC950 treatment. Conclusion: Here we demonstrate that treatment with MCC950 in the AAV1/2-A53T-αSyn mouse model can significantly reduce neuroinflammation and acts neuroprotective.